Comprehensive Assessment of Physicochemical and Microbiological Water Quality Indexing with Antibiotic Resistance Profiling of Escherichia coli in the Bagmati River, Kathmandu, Nepal - Puspa Raj Dahal; Rajendra D. Joshi (The Bioscan, 2025)
The Bagmati River, a crucial waterway in Kathmandu, Nepal, has been severely impacted by rapid urbanization, industrial discharge, and untreated sewage, leading to significant pollution. This study investigates the physicochemical water quality of the Bagmati River and the antibiotic resistance patterns of Escherichia coli (E. coli), a key fecal indicator bacterium. Water samples were collected from various sites along the River from Sundarijal to Chovar, Kathmandu, during two periods: January–June 2020–21 and July–December 2020–21. Key physicochemical parameters analysed included temperature, pH, Total Suspended Solids (TSS), Dissolved Oxygen (DO), Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), total nitrogen, phosphorus, nitrate, and heavy metals (Cu, Pb, Zn, Cd, Cr, Hg). Most of the samples cross the limit of both WHO and Nepal standard. Results revealed TSS levels ranging from 113–444 mg/L and 68–513 mg/L, and BOD values of 1.5–394 mg/L and 1.5–392.8 mg/L for January–June and July–December, respectively, both exceeding WHO and Nepalese standards. Coliform counts ranged from 0.18×10²–148.6×10² CFU/mL and 0.2×10²–126×10² CFU/mL in the respective periods, indicating bacterial contamination from untreated waste. Antibiotic sensitivity testing of E. coli isolates (E1–E28) revealed high resistance to ampicillin (87%) and erythromycin (90%). Conversely, ciprofloxacin, chloramphenicol, nitrofurantoin, and gentamicin exhibited strong effectiveness, with inhibition zones ranging from 12–38 mm, 16–30 mm, 16–26 mm, and 18–23 mm, respectively. Intermediate resistance to tetracycline and ceftriaxone suggests emerging resistance patterns. These findings underscore the dual challenges of water pollution and antibiotic resistance, emphasizing the urgent need for wastewater treatment, stricter regulation of industrial discharges, and prudent antibiotic use to safeguard public and environmental health.